Kemampuan Alat Kincir Angin Sederhana Dalam Menghasilkan Listrik - Singgih Bektiarso; I Ketut Mahardika; Nuril Martha Anggraeni; Retno Enggar kinasih; Nur Azizatul Jannah (Peneliti.net, 2023)
The turbine (turbine) can rotate as a boost from rotation which can be continued so that it can be used to rotate part of the windmill generator into electrical energy. Wind power plants as a potential have the Indonesian nation as a renewable electrical energy with a large enough. The purpose of this study was to find out the potential of wind as a Wind Power Plant (PLTA) as an alternative to electricity. Data collection techniques were obtained from literature review studies on library research or descriptive document studies (Library Research) from various types of documents that support the research theme, namely laws, books, journals and articles. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results of the study show that not all windmills provide benefits and are alternative sources of electricity.